Lie in plain sight : a thriller - Barbieri, Maggie (Barbieri, Maggie. Maeve Conlon novels., 2016)
"It's a busy day at the bakery Maeve Conlon owns when she receives a phone call from the high school saying Maeve's employee's daughter, Taylor Dvorak, is ill. Taylor's mom is out on a delivery and Taylor has her own car, so harried Maeve gives the school nurse permission to send Taylor home on her own. But Taylor never makes it home. Somewhere between the school and her house, she just vanishes. Not only does Maeve feel responsible, but she can't shake the feeling that there's more to Taylor's disappearance than meets the eye. So Maeve decides to take matters into her own capable hands. Balancing this dark undertaking and her relationship with a local policeman, Maeve carefully walks the fine line between justice and revenge in the next suspenseful novel from Maggie Barbieri"--